Laboratory abnormalities in children with mild and severe coronavirus disease 2019 (COVID-19): A pooled analysis and review - Henry, Brandon Michael; Benoit, Stefanie W.; de Oliveira, Maria Helena Santos; Hsieh, Wan Chin; Benoit, Justin; Ballout, Rami A.; Plebani, Mario; Lippi, Giuseppe (Clinical biochemistry, 2020)
•No clear pattern of leukocyte abnormalities is seen in children with COVID-19.•Leukocyte counts may not be a reliable marker of pediatric COVID-19 severity.•C-Reactive Protein and Lactate Dehydrogenase are frequently elevated in severe cases.•Procalcitonin is often elevated and may reflect bacterial co-infection.•Elevated creatine kinase-MB is seen in one-third of children with mild COVID-19. Limited data exists to-date on the laboratory findings in children with COVID-19, warranting the conduction of this study, in which we pool the currently available literature data on the laboratory findings seen in children with mild and severe COVID-19. Following an extensive literature search, we identified 24 eligible studies, including a total of 624 pediatric cases with laboratory-confirmed COVID-19, which report data on 27 different biomarkers. We then performed a meta-analysis to calculate the pooled prevalence estimates (PPE) for these laboratory abnormalities in mild COVID-19. As data was too limited for children with severe COVID-19 to allow pooling, results were presented descriptively in a summary of findings table. Our data show an inconsistent pattern of change in the leukocyte index of mild and severe cases of COVID-19 in children. Specifically, changes in leukocyte counts were only observed in 32% of the mild pediatric cases (PPE: 13% increase, 19% decrease). In mild disease, creatine kinase-MB (CK-MB) was frequently elevated, with a PPE of 33%. In severe disease, c-reactive protein (CRP), procalcitonin (PCT), and lactate dehydrogenase (LDH) were frequently elevated. Based on data obtained from early COVID-19 studies, leukocyte indices in children appear inconsistent, differing from those reported in adults that highlight specific leukocyte trends. This brings into question the utility and reliability of such parameters in monitoring disease severity in the pediatric population. Instead, we suggest physicians to serially monitor CRP, PCT, and LDH to track the course of illness in hospitalized children. Finally, elevated CK-MB in mild pediatric COVID-19 cases is indicative of possible cardiac injury. This highlights the importance of monitoring cardiac biomarkers in hospitalized patients and the need for further investigation of markers such as cardiac troponin in future studies.